Military Politics and Democracy in the Andes - Jaskoski, Maiah, 1977- (Book collections on Project MUSE., 2013)
Interviews with active-duty and retired military officers in Ecuador and Peru shed light on the evolution of Andean civil-military relations, with implications for democratization. This study challenges conventional theories regarding military behavior in post-transition democracies. Through a deeply researched comparative analysis of the Ecuadorian and Peruvian armies, the author argues that militaries are concerned more with the predictability of their missions than with sovereignty objectives set by democratically-elected leaders.